Journal of management development : the unfulfilled promise of responsible management education - Cornuel, Eric; Hommel, Ulrich (Journal of Management Development: Volume 34, Issue 1., 2015)
There is abundant evidence that RME is (so far) a largely unfulfilled promise. While business schools have been active in adding organizational ""bells and whistles"" (dedicated courses, institutes/centres), the core of their research and teaching activities still appears largely immune to the challenge of addressing societal concerns more broadly (Hommel, Painter-Morland, & Wang, 2012). The purpose of this e-book is to analyse the barriers preventing RME from creating a more visible imprint on management education and to identify ways of overcoming them. To some extent, it turns the existing